HUBUNGAN USIA DAN JUMLAH PARITAS DENGAN TIPE KARSINOMA ENDOMETRIUM DI RSUD PROF. DR. MARGONO SOEKARJO - Nusa, Arifah Pelangi; Nawangtantrini, Gita; Aditiyono, Aditiyono; Novrial, Dody; Yamsum, M (Fakultas Kedokteran Universitas Jenderal Soedirman, 2023)
Background: Endometrial cancer ranks 15th with the highest number of new cases in 2020 in the world. There are still differences in research results regarding the relationship between age and number of parities with endometrial carcinome. Aim: To determine the relationship between age and parity with type of endometrial carcinoma at RSUD Prof. Dr. Margono Soekarjo. Method: This research is an observational analytic study with a cross sectional study. The sampling technique uses total sampling. Total subjects were 129 endometrial carcinoma patients at RSUD Prof. Dr. Margono Soekarjo in 2017-2022. The data taken is secondary data from the medical records. The variable age and number of parities are the data listed in the medical record document. Data were analyzed using the chi-square statistical test. Result: The total sample obtained was 129 patients. The most common age was found at the age of 51-60 years (41.1%) and the least at the age of <40 years (7.8%). The highest number of parities found was parity ≥2 (55.8%) and the least was parity 1 (15.5%). The results of the chi-square statistical test for age with endometrial carcinoma type showed a value of p = 0.159 (p>0.05). Based on the results of the analysis, there was no significant relationship between age and the type of endometrial cancer. The results of the chi-square statistical test for the number of endometrial carcinoma types showed a value of p = 0.02 (p <0.05). Based on the results of the analysis, it showed that there was a significant relationship between the number of parities and the type of endometrial cancer. Conclusion: There was no significant relationship between age and the type of endometrial carcinome and there was a significant relationship between the number of parities and the type of endometrial carcinome at RSUD Prof. Dr. Margono Soekarjo.